Waterborne Polyurethane Enhanced, Adhesive, and Ionic Conductive Hydrogel for Multifunctional Sensors. Issue 22 (13th October 2021) - Li, Xiaobin; Zhang, Ending; Shi, Jun; Xiong, Xiaoyan; Lin, Jiaming; Zhang, Qiang; Cui, Xiaohua; Tan, Liqin; Wu, Kun
Abstract: In the past two decades, ionic conductive hydrogel has attracted tremendous research interests for their intrinsic characteristics in the field of flexible sensor. However, synchronous achievement of high mechanical strength, satisfied ionic conductivity, and broad adhesion to various substrates is still a challenge. Herein, a novel zwitterionic composite hydrogel that displayed excited strechability (up to 900%), satisfied strength (about 30 kPa), high ionic conductivity (1.2 mS cm −1 ), and adhesion to polar and nonpolar materials is fabricated though the combination of waterborne polyurethanes (PU) and poly(sulfobetaine zwitterion‐ co ‐acrylamide) (SAm). Especially, this facile strategy demonstrates that PU has a synergistic effect on enhancing mechanical strength and ionic conductivity for ionic conductive hydrogel. Moreover, the hydrogel‐based strain/stress sensor shows high sensitivity, wide sensing range, great stability, and accuracy for human body movements detecting and voice recognition. This novel ionic conductive hydrogel has promoted the development of wearable devices. Abstract : In recent years, the preparation of ion‐conductive hydrogel that achieves high mechanical strength and satisfactory ionic conductivity at the same time has attracted more and more research interests. Here, a novel hydrogel is facilely fabricated that demonstrated a synergistic effect of waterborne polyurethanes in boosting both mechanical properties and ionic conductivity, which paves the way for developing high‐performance wearable devices.